Problems of Immanence: studies critical and constructive - Warschauer, Joseph, 1869- (Salt Lake City, UT : Project Gutenberg, 2007)
"Problems of Immanence: Studies Critical and Constructive" by Joseph Warschauer is a theological examination written in the early 20th century. This work engages with the doctrine of Divine immanence, exploring its philosophical implications and addressing prevalent misconceptions surrounding it. The author seeks to differentiate genuine interpretations of immanence from its misrepresentations, ultimately arguing for the preservation of the idea of a personal, transcendent God. The opening of this text presents the author's motivation and the historical context of the doctrine of Divine immanence, which Warschauer asserts has gained renewed attention yet suffers from misinterpretation. He emphasizes the critical need to "safeguard and vindicate" essential tenets of faith, including God's personal nature and the existence of evil, from the errors of an overly monistic philosophy. Throughout the preface and introduction, the author sets the stage for a detailed exploration of various theological positions, setting his book within a broader conversation on the interface between modern thought and religious belief. (This is an automatically generated summary.)
Release date is 2007-05-16
Produced by Al Haines
Keywords: Immanence of God